Animal Protection in the Perspective of Positive Law and Islamic Law: A Study of Elephant-Human Conflict in Aceh, Indonesia - Efendi, Efendi; Zuhri, M; Tarmizi, Tarmizi; Hadi, Ainal; Yunanda, Rizki (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This article talks about protecting animals from the point of view of positive law and Islamic law. It focuses on elephants and their conflicts with people. Cases of conflict between elephants and humans have continued to increase from 2015 to 2021, reaching 582 cases. This research is a normative legal study, while the approach used is the approach of legislation and Islamic law. The data studied are literature and legal norms related to positive legal rules and Islamic law. This study concludes that the government has made efforts to protect elephants by issuing various laws and regulations, both at the central and regional levels. Positional law regulates and strives for the protection of elephants, such as the prohibition of catching, injuring, killing, possessing, keeping, and even trading them. In addition, the government has taken various steps, including having mutual coordination between related agencies, involving non-governmental organizations and the community, and enforcing the law. Furthermore, to overcome conflicts between elephants and humans in the future, it is necessary to immediately implement policies related to the prohibition of land use around elephant crossings and policies to relocate people close to elephant crossing areas and provide compensation to those who are affected. From the perspective of Islamic law, the protection of animals, including elephants, is part of the benefit based on the Qur'an, hadith, and fatwas of ulemas to preserve nature, which has an impact on human survival.